Parents' perception of the promotion of physical activity as part of the Purzelbaum project in Swiss daycare centers - Bianca Celine Schmidli; Claudio R. Nigg (Current Issues in Sport Science)
Introduction Already in early childhood, physical activity (PA) is important for healthy development. Parents are a significant influencing factor on PA behavior (Su et al., 2022), and are therefore, involved in the “Purzelbaum”-daycare project to promote PA (radix, 2011). Purzelbaum is a one-and-a-half-year training program that certifies “movement-friendly” daycare centers upon completion. This study examines whether the participation and perception of PA by parents differs in daycare centers with or without Purzelbaum certification.